Policy, Regulation, and Patient Safety: A Review of Global Efforts to Improve Healthcare Quality - ALHAHRBI, REHAB SAAD; ALHAHRBI, HAYA SALEM; ALNOMSI, JAMLA HAZZA; AL-NOUMSI, HESSAH SAAD FALAH; AL-HARBI , MODI HALIL ABDULLAH; ALENAZI, MEZNAH HENDI; ALNAS, ZAHRA ALI; ALNASSAR, HEND ALI; ALOTAIBI, NASSER EID SAAD; ALOTAIBI, NORAH NASSER; GHANDOORA, DR.LUAI KHALIL; ALQARNI, FAISAL DAIFALLAH (Journal of Posthumanism, 2024)
The future of hospital safety lies in a balanced integration of smart technologies, policy reform, workforce engagement, and ethical oversight. Innovations such as AI, wearables, and remote systems are reshaping safety protocols and enabling hospitals to transition from reactive to proactive safety management. Strengthened mental health support, global collaboration, and continuous education further protect and empower healthcare professionals (Zhang et al., 2021; Fotis, 2022). By adopting a forward-looking approach that leverages technology while preserving human-centered care, hospitals can build a resilient, adaptive, and safe environment for both staff and patients.